2020
DOI: 10.3390/foods9040483
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Nutritional Composition of Matcha Green Tea

Abstract: Matcha green tea (Camellia sinensis), which originates from Japan, is commonly considered as particularly beneficial to health. A large content of polyphenols, amino acids (mainly tannins) and caffeine potentially increase the antioxidant properties of the drink. The aim of the study was to determine the antioxidant potential and the content of substances with an antioxidant effect—vitamin C, total polyphenol content including flavonoids—in infusions made from Traditional Matcha (from the first and second harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 50 publications
7
82
2
Order By: Relevance
“…The authors contrasted the level of rutin found in matcha (1968.8 mg/L) with that in buckwheat (62.30 mg/100 g), the latter being recognised as one of the richest sources of rutin in the human diet, and demonstrated that matcha tea may be a better source of the compound than other foodstuffs. The findings made by Jakubczyk et al [ 36 ] appear to be consistent with the observations of Koláčková et al [ 27 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teasupporting
confidence: 89%
See 3 more Smart Citations
“…The authors contrasted the level of rutin found in matcha (1968.8 mg/L) with that in buckwheat (62.30 mg/100 g), the latter being recognised as one of the richest sources of rutin in the human diet, and demonstrated that matcha tea may be a better source of the compound than other foodstuffs. The findings made by Jakubczyk et al [ 36 ] appear to be consistent with the observations of Koláčková et al [ 27 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teasupporting
confidence: 89%
“…Rutin, which is a polyphenolic compound, is a potent antioxidant. Its synergistic interaction with ascorbic acid may enhance the protective effects of both substances in the cardiovascular system, strengthening blood vessels [ 36 ]. It also has antidiabetic and anti-inflammatory properties, thus preventing diabetes-related pathologies [ 37 , 38 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teamentioning
confidence: 99%
See 2 more Smart Citations
“…Results of SRB assay recorded from trophozoites treated with a range of concentrations of matcha, and particularly those treated with the highest concentration (100%) had a significantly lower optical density (i.e., reduced growth rate of trophozoites) compared with those that were incubated in PYG medium alone. Previous studies showed that antioxidant capabilities and the content of phenolic compounds of green tea and matcha tea are increased with increasing the water temperature used for the preparation of the infusion/brew, with the highest values achieved at 100 • C [10] and 90 • C [11]. In our study, similar results were obtained by testing the effect of hot and cold brews, suggesting that brewing temperature does not seem to influence the matcha anti-acanthamoebic activity, or that the effector substance(s) in matcha are not affected by heat.…”
Section: Discussionmentioning
confidence: 99%